Referral patterns and diagnostic outcomes in an outpatient Australian tertiary cognitive neurology service: 2009–2019 - Antony Sutherland; Christopher Kyndt; David Darby; Maja Christensen; Fari Islam; Samantha M. Loi; Amy Brodtmann (Alzheimer’s & Dementia: Diagnosis, Assessment & Disease Monitoring, 2025)
Abstract Introduction Young‐onset dementia (YOD) and atypical dementias often experience diagnostic delays, particularly in outpatient settings where timely referrals are crucial. Methods A 10‐year retrospective audit (2009–2019) of 626 patients at a specialist cognitive neurology clinic reviewed demographics, referral sources, and time to diagnosis. Data were compared between YOD and late‐onset dementia (LOD), and with and without dementia groups. Results Fifty‐three percent of patients were diagnosed with dementia (mean age: 65 ± 11.9 years). Non‐neurodegenerative conditions were more frequent in < 65 years (61%). Among YOD cases, Alzheimer's dementia (AD) and behavioral variant frontotemporal dementia accounted for 40% and 34% of diagnoses, respectively, while AD predominated in LOD (65%). Language‐variant dementias were similar between groups (14%). Diagnostic delays in YOD averaged 1 year longer than in LOD. Discussion Higher YOD and language‐variant dementia referrals to specialist services reveal diagnostic delays, underscoring the need for better referral and diagnostic pathways. Highlights Delayed diagnosis common in young‐onset dementia (YOD) and atypical dementia. Specialist clinics see more YOD and language‐variant dementia referrals. YOD has longer time from symptom onset to diagnosis compared to late‐onset cases. Behavioral variant frontotemporal dementia (bvFTD) a more common diagnosis in YOD patients.